The psychological effects of poverty on investments in children's human capital - Guilherme Lichand; Eric Bettinger; Nina Menezes Cunha; Ricardo Madeira (University of Zurich, Department of Economics, 2020)
Poverty focuses attention on present needs. Does that mean that poor parents respond inefficiently to future returns on investments in their children's human capital - even when they would have the financial means to invest optimally? We study this question in the context of an educational program in Brazil whose predicted child-specific returns are known to the researchers, allowing us to compute optimal decisions. Using a lab-in-the-field experiment to make some parents worry more than others about pressing financial needs, we find that those in the treatment condition offered the opportunity to invest in that program misallocate resources relative to the control group: they not only invest significantly less when the program has high returns, but also, significantly more when predicted returns are low. We show that such inefficient responses are driven by poverty-induced attention misa/Jocation, since (1) parents in the treatment condition perform better in cognitive tests that yield small but immediate returns, and (2) increasing the salience of returns before the experiment eliminates differential responses by those parents. Our results suggest that poiicy instruments to boost human capital investments among the poor, such as credit lines earmarked for education, may be insufficient to spark such investments when returns are high, and even lead to over-investment by those not expected to benefit from it.
Keywords: C93; D91; E24; I25; I26; 330; psychology of poverty; attention misallocation; human capital; poverty trap